2023
DOI: 10.1128/spectrum.04542-22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rapid Antigen Detection Test for Diagnosing SARS-CoV-2 during the COVID-19 Pandemic: Experience from a Centralized Isolation Site in Shanghai, China

Abstract: RADTs have demonstrated excellent performance in many counties for screening SARS-CoV-2 infection, but very few studies have been conducted in China. The performance of RADTs is largely related to different real-life scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It was reported that sensitivities of DART were 78.4% for participants within 5 days after the first RT‐PCR‐positive result and 90.77% even higher within 5 days after symptom onset in a Chinese cohort. 22 And more importantly, nasopharyngeal swabs were better than oropharyngeal (throat) swab at sensitivity detection, especially in early stages of infection and in asymptomatic patients. 29 So, in our research design, nasopharyngeal swabs were mandatory, both for DART and RT‐PCR, and DART results were approved for the diagnosis of COVID‐19.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It was reported that sensitivities of DART were 78.4% for participants within 5 days after the first RT‐PCR‐positive result and 90.77% even higher within 5 days after symptom onset in a Chinese cohort. 22 And more importantly, nasopharyngeal swabs were better than oropharyngeal (throat) swab at sensitivity detection, especially in early stages of infection and in asymptomatic patients. 29 So, in our research design, nasopharyngeal swabs were mandatory, both for DART and RT‐PCR, and DART results were approved for the diagnosis of COVID‐19.…”
Section: Discussionmentioning
confidence: 98%
“…Patients were quickly admitted to hospitals if they met the criteria of moderate or severe illness according to World Health Organization (WHO) clinical progression scale of COVID‐19 infection 21 . Patients with uninfected or mild disease, including asymptomatic disease, were encouraged to stay at home, apply individual protections, and daily direct antigen rapid test (DART) for COVID‐19 22 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations